Oliver Twist stage 6 (2500 headwords) - Dickens Ch. Charles (Oxford Bookworms Library)
The elegant verse and subtle observation of the Amores, The Art of Love, and The Cures of Love made their author the talk of Rome. Ovid saw love as a game at which both sexes could play without getting hurt - as long as they stuck to his rules, but primarily he wrote these sparkling and often erotic poems to entertain, and after two thousand years they still give enormous pleasure.